Meningkatkan Hasil Belajar Peserta Didik Agama Hindu Kelas III Menggunakan Media Wordwall di SD Negeri 2 Wosu Kecamatan Bungku Barat Kabupaten Morowali Provinsi Sulawesi Tengah - Ni Made Samiadi (Jurnal Riset Multidisiplin Edukasi, 2024)
This study aims to determine the impact of using Wordwall media on the learning outcomes of IIIrd-grade students at SD Negeri 2 Wosu, Bungku Barat District, Morowali Regency, Central Sulawesi. Wordwall was selected as an innovative solution to enhance student motivation and engagement in learning. The research uses a qualitative approach with a descriptive design, through observation and tests of student learning outcomes before and after using Wordwall media. The results show that the use of Wordwall has a positive impact on improving students' learning outcomes, with a significant increase in students' average test scores after the implementation of this media. In addition, students also showed increased engagement and higher enthusiasm during the learning process. However, there are some challenges to consider, such as dependence on technological devices and the limitations of the types of games that can be adapted to all types of content. Overall, the use of Wordwall can be an effective media for improving the quality of learning, especially at the elementary school level.